2022
DOI: 10.7759/cureus.30369
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Dialysis Patients in the Central Region of Morocco: What Is the Health-Care Delay?

Abstract: Introduction: Due to the predominantly cellular immunosuppression, infections are frequent in chronic dialysis patients, in particular tuberculosis (TB). The main objective of our study is to evaluate tuberculosis healthcare delay in dialysis patients and to raise the diagnostic challenge in these patients. Material and methods: The study is retrospective and multicenter including tuberculosis cases of chronic dialysis patients either in hemodialysis (HD) or peritoneal dialysis (PD) in the central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…La Tb est une maladie infectieuse qui complique, de nombreux terrains immunodéprimés tels que les patients en insuffisance rénale chronique terminale et en dialyse. Elle est plus fréquente dans les pays endémiques de Tb avec une incidence arrivant à 4200/10000 dialysé par rapport à une région endémique à moins de 100/100000 dialysé [2,4,5,6].…”
Section: Discussionunclassified
“…La Tb est une maladie infectieuse qui complique, de nombreux terrains immunodéprimés tels que les patients en insuffisance rénale chronique terminale et en dialyse. Elle est plus fréquente dans les pays endémiques de Tb avec une incidence arrivant à 4200/10000 dialysé par rapport à une région endémique à moins de 100/100000 dialysé [2,4,5,6].…”
Section: Discussionunclassified
“…Early diagnosis and early initiation of treatment are necessary to improve the prognosis, but diagnosis is often difficult. Dialysis patients from Morocco also reported that it takes a long time from the appearance of symptoms of tuberculosis to the diagnosis and initiation of treatment [11]. In the case of pulmonary tuberculosis, coughing, expectoration of sputum, and the appearance of new shadows in the lung fields are the triggers for suspicion of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of TB in dialysis patients appears to be higher as well [13]. This may be commonly associated with late diagnosis and treatment, which, in turn, is due to the nonspecific symptoms of TB in dialysis patients, whereas the involvement is often extrapulmonary [13,14].…”
Section: Introductionmentioning
confidence: 99%